Bilateral serous surface papillary borderline ovarian tumor with non-invasive implantation: a case report - Wang, Zhengping; Gao, Sumei; Wei, Shuli; Jiang, Yina; Li, Mengling (Frontiers in Oncology, 2026)
IntroductionSerous surface papillary borderline ovarian tumors (SSPBOTs), a clinically distinct variant of serous borderline ovarian tumors (SBOTs), are frequently misdiagnosed as malignant tumors during preoperative diagnostic assessments.Presentation of caseThis case report describes a 22-year-old female patient who presented with abdominal pain. Gynecological examination revealed a painless 11-cm diameter mass on the right posterior side of the uterine body. Ultrasonography demonstrated a solid mass in the right ovary (O-RADS 5, highly indicative of malignant germ cell tumor). It also revealed a unilocular cystic mass in the left ovary (O-RADS 2, with benign characteristics). During the operation, a cauliflower-like mass was observed on one side of the surface of the right ovary. On the left ovary, a cystic mass was found, with multiple small cauliflower-like masses scattered on its surface. Additionally, pelvic cavity examination revealed millet-sized lesions and fibrinous exudate. The pathological diagnosis confirmed the presence of bilateral serous borderline tumors with multiple non-invasive implants. Treatment involved the excision of bilateral ovarian masses and the resection of secondary lesions. No evidence of recurrence was observed during the one-year follow-up.DiscussionSSPBOTs are a distinct subtype of serous borderline ovarian tumors that predominantly affecting women of reproductive age and often involve bilateral ovaries. Ultrasound findings mostly show solid hypoechoic masses growing on the surface of the ovary. These masses surround normal ovarian tissue and exhibit a visible “microcystic sign” within. Punctate strong echoes or coarse calcified spots may also be observed. Color Doppler ultrasound demonstrates abundant intratumoral vascularity with a ‘firework-like’ perfusion pattern. Insufficient understanding of this disease can easily lead to misdiagnosis as a germ cell tumor. Although CA-125 levels may be elevated, the marker lacks diagnostic specificity. Given the tumor’s indolent growth pattern and low recurrence rate, fertility-sparing surgery is feasible for patients desiring reproductive preservation.ConclusionThis report systematically summarizes the ultrasonographic characteristics of SSPBOTs, aiming to enhance diagnostic accuracy and provide evidence-based support for fertility preservation strategies in young patients.